Análisis de las complicaciones postoperatorias en el tratamiento quirúrgico de la Hernia Inguinal. - Donoso Flores, Melanie Dayana (2025)
Inguinal hernia is a common surgical condition characterized by the protrusion of abdominal contents through a weakness in the abdominal wall. Surgical intervention remains the mainstay of treatment, with the most widely used techniques being open hernia repair (Lichtenstein) and laparoscopic approaches, such as transabdominal preperitoneal (TAPP) and totally extraperitoneal (TEP) repair. Although both methods are considered safe and effective, postoperative complications can occur and may impact patient recovery. This study presents a systematic review of scientific literature published between 2020 and 2025, aiming to analyze the most prevalent postoperative complications associated with these surgical techniques, identify risk factors contributing to their development, and compare the incidence of complications between methods. A total of 20 studies were included, selected based on rigorous inclusion and exclusion criteria. The most frequently reported complications were seroma formation, surgical site infection, hematoma, and chronic pain. Risk factors associated with a higher incidence of these complications included advanced age, comorbidities such as hypertension, diabetes mellitus, and cardiovascular disease, toxic habits like smoking, a body mass index (BMI) ≥ 25 kg/m³, intraoperative adhesions, blood loss exceeding 8 ml, a history of prior inguinal surgeries, and the presence of recurrent hernias. In comparing surgical techniques, no significant differences were observed in terms of recurrence rates or overall complication incidence. However, distinct complication profiles emerged: the Lichtenstein technique was associated with a greater tendency toward seroma formation, infection, and persistent postoperative pain, whereas laparoscopic approaches were linked to reduced postoperative pain, faster recovery times, and lower rates of chronic discomfort. These findings underscore the importance of tailoring the choice of surgical technique to the patient's individual clinical characteristics. Furthermore, they highlight the need for structured postoperative follow-up protocols to optimize outcomes and minimize complications associated with this prevalent surgical procedure.